Evaluation of ForenSeq DNA signature kit for Qatari population. (December 2017) - Almohammed, E.; Iyengar, A.; Ballard, D.; Devesse, L.; Hadi, S.
Abstract: Recent advances in Massively Parallel Sequencing (MPS) provide advantages over previously used technologies to analyse DNA samples in terms of speed and number of DNA markers that can be analysed simultaneously. The aim of this study was to evaluate the Illumina ForenSeq DNA signature kit and MiSeq FGx platform. The beta-version of the kit was used to genotype 150 Qatari samples that had been profiled using GlobalFiler™ kit on the ABI 3500. This study serves as the first investigation of Qatari population using the MPS methods.